2022
DOI: 10.1111/1471-0307.12913
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric spectroscopy‐based characterisation of different types of Paneer (Indian cottage cheese) in terms of texture, microstructure and functional groups

Abstract: Different variants of Paneer were prepared with cow milk (CM), buffalo milk (BM), skimmed milk powder (SMP) and blends (40:60, 50:50, 60:40) of SMP with CM/BM. The Paneer composition, texture, microstructure and spread of functional groups were correlated with the dielectric capacitance values. Results depicted a strong correlation (R2 > 0.95) between milk used for Paneer making and its proximate composition in terms of the capacitance value, and it was highest for CM followed by BM; 100% SMP Paneer recorded l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…The moisture content of Paneer made from 100% SMP was found to be the highest (61.03%-62.93%). This increase in moisture content is consistent with the findings of Kumari et al (2023) It was observed that capacitance of pure buffalo milk Paneer was highest (192.58 μF) in spite of having low moisture content (Table 3).…”
Section: Evaluation Of Working Performance Of the Developed Sensor-ba...supporting
confidence: 91%
See 4 more Smart Citations
“…The moisture content of Paneer made from 100% SMP was found to be the highest (61.03%-62.93%). This increase in moisture content is consistent with the findings of Kumari et al (2023) It was observed that capacitance of pure buffalo milk Paneer was highest (192.58 μF) in spite of having low moisture content (Table 3).…”
Section: Evaluation Of Working Performance Of the Developed Sensor-ba...supporting
confidence: 91%
“…Different types of Paneer (Table 1) were prepared as per the method described by Kumari et al (2023). Each type of Paneer was made three times, and data were recorded in three replicates for each sample.…”
Section: Paneer Making Processmentioning
confidence: 99%
See 3 more Smart Citations